Two-sided matching model of service providers and demanders considering peer and synergy effects - Tiaojuan Han; Jianfeng Lu; Hao Zhang (Heliyon, 2023)
In cloud manufacturing, the dynamic characteristics of manufacturing services increase the complexity of supply and demand matching. A peer effect between service demanders and a synergy effect between service providers affect the final matching result. This paper proposes a two-sided matching model of service providers and demanders considering the peer and synergy effects. First, a dynamic evaluation index system is proposed, and the index weight of service providers and demanders is determined based on the fuzzy analytical hierarchy process. Second, a two-sided matching model is established based on peer and synergy effects. Finally, the proposed method is validated by the collaborative manufacturing of hydraulic cylinders. The results reveal that the model effectively matches service demanders with service providers, improving the overall satisfaction of both parties.